The Oxford handbook of corporate reputation - Barnett, Michael L.; Pollock, Timothy G. (Oxford : Oxford University Press, 2012)
This handbook offers a diverse set of scholarly perspectives on the nature of corporate reputation: what it is, where it comes from, and how it may be managed to create and protect corporate as well as societal value.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Corporate image